Questions and answers about weather - Craig, M. Jean.; Ebert, Len (New York : Scholastic, 1996)
Answers questions about such everyday aspects of the weather as rain, snow, wind, fog, and heat, and briefly looks at methods of weather forecasting.
4.8
3-6
Keywords: Weather; Weather